Control of Progesterone Receptor-A Transrepressive Activity in Myometrial Cells: Implications for the Control of Human Parturition. (February 2018) - Patel, Bansari; Peters, Gregory A.; Skomorovska-Prokvolit, Yelenna; Yi, Lijuan; Tan, Huiqing; Yousef, Ahmed; Wang, Junye; Mesiano, Sam
Uterine quiescence during pregnancy is maintained by progesterone primarily via signaling mediated by the type-B progesterone receptor (PR-B) in myometrial cells. Withdrawal of PR-B-mediated progesterone activity is a principal trigger for labor. One mechanism for PR-B withdrawal is by inhibition of its activity by the type-A PR (PR-A) isoform in myometrial cells. We hypothesized that human parturition involves hormonal interactions that induce the capacity for PR-A to inhibit PR-B in myometrial cells and that pro-inflammatory cytokines are major regulators of this process. We tested this hypothesis in an immortalized human myometrial cell line, hTERT-HM A/B, in which levels of PR-A and PR-B can be experimentally controlled. We found that the capacity for PR-A to repress PR-B, assessed by activity of a transiently transfected reporter DNA controlled by the progesterone response element, and expression of FK506 binding protein 5 ( FKBP5 ) an endogenous PR-B responsive gene, was increased by serum supplementation and interleukin-1β. In pregnant uterus, FKBP5 was detected exclusively in myometrial cells and its expression decreased with advancing gestation and in association with the onset of labor at term. These findings suggest that in myometrial cells the repressive activity of PR-A on PR-B increases with advancing gestation and is induced by pro-inflammatory cytokines. This may be a key mechanism linking inflammation with the onset of labor.